Raman scattering studies of composites based on Cu₆PS₅X (X = I, Br) superionic nanocrystals - Studenyak, I.P.; Kranjčec, M.; Buchuk, R.Yu.; Stephanovich, V.O.; Kökényesi, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Composites were prepared by mixing Cu₆PS₅X (X = I, Br) nanocrystalline
powders obtained by ball milling with different polymers. The average nanocrystal size
was estimated from X-ray diffraction; the composites were studied by scanning electron
microscopy. Phonon spectra of nanocomposites with different polymer matrices, size and
concentration of nanocrystals were studied using Raman spectroscopy. It has been
revealed that the surface-to-bulk phonon integrated intensity ratio strongly varies with
the type of polymer matrix, average grain size and concentration of nanocrystals